Genetic Characterization of Optochin-Susceptible Viridans Group Streptococci - Martín-Galiano, Antonio J. (American Society for Microbiology, 2003)
Two clinical isolates of viridans group streptococci (VS) with different degrees of susceptibility to optochin (OPT), i.e., fully OPT-susceptible (Opt(s)) VS strain 1162/99 (for which the MIC was equal to that for Streptococcus pneumoniae, 0.75 μg/ml) and intermediate Opt(s) VS strain 1174/97 (MIC, 6 μg/ml) were studied. Besides being OPT susceptible, they showed characteristics typical of VS, such as bile insolubility; lack of reaction with pneumococcal capsular antibodies; and lack of hybridization with rRNA (AccuProbe)-, lytA-, and pnl-specific pneumococcal probes. However, these VS Opt(s) strains and VS type strains hybridized with ant, a gene not present in S. pneumoniae. A detailed characterization of the genes encoding the 16S rRNA and SodA classified isolates 1162/99 and 1174/97 as Streptococcus mitis. Analysis of the atpCAB region, which encodes the c, a, and b subunits of the F(0)F(1) H(+)-ATPase, the target of optochin, revealed high degrees of similarity between S. mitis 1162/99 and S. pneumoniae in atpC, atpA, and the N terminus of atpB. Moreover, amino acid identity between S. mitis 1174/97 and S. pneumoniae was found in α helix 5 of the a subunit. The organization of the chromosomal region containing the atp operon of the two Opt(s) VS and VS type strains was spr1284-atpC, with spr1284 being located 296 to 556 bp from atpC, whereas in S. pneumoniae this distance was longer than 68 kb. In addition, the gene order in S. pneumoniae was IS1239-74 bp-atpC. The results suggest that the full OPT susceptibility of S. mitis 1162/99 is due to the acquisition of atpC, atpA, and part of atpB from S. pneumoniae and that the intermediate OPT susceptibility of S. mitis 1174/97 correlates with the amino acid composition of its a subunit.